Effectiveness of high efficiency particulate (HEPA) air condition combined with the antifungal prophylaxis on incidence, morbidity and mortality of invasive fungal infections in patients with acute myeloid leukemia: a retrospective single-center study - Preyer, Linda; Vettorazzi, Eik; Fiedler, Walter; Rohde, Holger; Stemler, Jannik; Gönner, Saskia; Bokemeyer, Carsten; Khandanpour, Cyrus; Wortmann, Friederike (Frontiers in Oncology, 2024)
IntroductionOur monocentric and retrospective study aimed to investigate the clinical effectivity of HEPA filters in combination with the antifungal drug prophylaxis in patients with AML undergoing intensive chemotherapy and allogeneic stem cell transplantation (SCT).Methods/ResultsWe included 177 patients between 2005 and 2015 representing a total of 372 in-hospital stays, 179 in the HEPA cohort (+HEPA) and 193 in the cohort without HEPA filters (-HEPA). No significant additional benefit of HEPA filtration on the risk reduction of IFI was observed. HEPA filtration did not significantly affect the risk of intensive care unit (ICU) admissions or early mortality rates. In patients who received allogeneic SCT in first complete remission with antifungal drug prophylaxis during prior induction treatment, a numerical but not significant improvement in long-term overall survival was noted in the +HEPA cohort compared to the -HEPA cohort (55% to 66%, p = 0.396). For better depicting of the clinical reality, we determined the so-called clinical suspected IFI (csIFI) -defined as cases with antifungal treatment after recommended prophylaxis without fulfilling current EORTC criteria. Especially in patients with a high risk for second IFI, significant risk reduction of csIFI and frequency of ICU admissions was observed when voriconazole was used as secondary antifungal prophylaxis. (csIFI, adjusted effect: OR 0.41, 95% CI (0.21 – 0.82), p = 0.01; csIFI, subgroup-specific effect: OR 0.35, 95% CI (0.15 – 0.78), p = 0.01; ICU, adjusted effect: OR 0.44, 95 CI (0.19 - 1.01), p = 0.05; respectively).DiscussionIn summary, the study suggests the efficacy of secondary antifungal prophylaxis in preventing IFI in AML patients undergoing intensive treatment. The addition of HEPA filtration also demonstrated additional numerous benefits in reducing the frequency of IFI-associated complications.